2018
DOI: 10.1016/j.jvs.2017.08.068
|View full text |Cite
|
Sign up to set email alerts
|

Standard “off-the-shelf” multibranched thoracoabdominal endograft in urgent and elective patients with single and staged procedures in a multicenter experience

Abstract: The first off-the-shelf multibranched endograft seems safe in both urgent/emergent and elective settings. The staged surgical approach appears to positively influence overall survival. This unique device and its operators will usher in a new treatment paradigm for TAAA repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…62 The outcomes of FEVAR and b-EVAR have been reported from various institutions. [62][63][64][65][66][67][68][69][70][71][72] Technical success was achieved in 90 to 97% of elective cases. The 30-day mortality was 0 to 9%, the occurrence rate of SCI was 4 to 12%, and the visceral vessel patency rate was 90 to 100%.…”
Section: Thoracoabdominal Aortic Aneurysmmentioning
confidence: 96%
“…62 The outcomes of FEVAR and b-EVAR have been reported from various institutions. [62][63][64][65][66][67][68][69][70][71][72] Technical success was achieved in 90 to 97% of elective cases. The 30-day mortality was 0 to 9%, the occurrence rate of SCI was 4 to 12%, and the visceral vessel patency rate was 90 to 100%.…”
Section: Thoracoabdominal Aortic Aneurysmmentioning
confidence: 96%
“…Stent grafts for F/BEVAR are custom made and therefore, take time to be prepared, whereas PMSG 9,10) and snorkel techniques 11) can be performed using off-the-shelf-devices and are suitable for emergency cases. Recent studies have reported using off-the-shelf devices, such as multibranched endografts or t-Branch (Cook Medical, Bloomington, IN, USA) 1214) and multilayer flow modulator stents (MFMS: Cardiatis, Isnes, Belgium) 15) as well. A hybrid surgery bypasses the abdominal branch and performs thoracic endovascular aortic repair (TEVAR).…”
Section: Endovascular Treatment Using Stent Graft For Thoracoabdominamentioning
confidence: 99%
“…In cases of visceral artery involvement, with more than two vessels, we always check for feasibility of an offthe-shelf complex solution. t-Branch from Cook is indicated for aneurysms with important proximal extension, and one of the most frequent reasons for unsuitability is generally the diameter of the aorta which should at least be 30 mm at the visceral segment [11]. In cases of unsuitability, we then look for a custom solution.…”
Section: Fevar and Bevarmentioning
confidence: 99%